Mechanism Matters: A Taxonomy of Cell Penetrating Peptides - Kauffman, W. Berkeley (Trends Biochem Sci, 2015)
The permeability barrier imposed by cellular membranes limits the access of exogenous compounds to the interior of cells. Researchers and patients alike would benefit from efficient methods for intracellular delivery of a wide range of membrane-impermeant molecules, including biochemically active small molecules, imaging agents, peptides, peptide nucleic acids, proteins, RNA, DNA, and nanoparticles. There has been a sustained effort to exploit cell penetrating peptides (CPPs) for the delivery of such useful cargoes in vitro and in vivo because of their biocompatibility, ease of synthesis, and controllable physical chemistry. Here, we discuss the many mechanisms by which CPPs can function, and describe a taxonomy of mechanisms that could be help organize future efforts in the field.